Investigating the relationship between quality education and gender equality in the light of sustainable development - Ali, Abdirahman Abdi; Alshraah, Shadi Majed; AlQarni, Khadijah (Research Journal in Advanced Humanities, 2024)
This study examines the relationship between Sustainable Development Goals (SDGs) 4 (Quality Education) and 5 (Gender Equality) within the context of Jordan. The research focuses on the quality of teacher training, ICT skills development, and the empowerment of women through technology. By employing a quantitative approach and hypothesis testing, the study identified five key variables: supply of qualified teachers (SQT), changes in teacher training (CTT), ICT skills and employability (TSE), participation of women in leadership (PWL), and women and technology in Jordan (WTJ). The data was gathered through a survey of 927 stakeholders, with results indicating positive correlations among these variables. These findings suggest a promising trend toward improving quality education and gender equality in Jordan. The participants had generally favourable perceptions, with mean scores ranging from 4.987 to 6.395, indicating a supportive attitude toward initiatives aimed at enhancing teacher quality. The study recommends targeted programs to improve teacher training in marginalized rural areas, emphasizing the critical role of ICT skills in bridging the employment gap. It also underscores the importance of female participation in leadership roles and the use of technology to combat gender inequality. Overall, this study provides valuable insights into Jordan's progress toward achieving SDGs 4 and 5, offering evidence-based recommendations to enhance educational quality and gender equality.